Tropical root and tuber crops: cassava, sweet potato, yams and aroids - Lebot, V.; Atherton, J.; Rees, A. (Wallingford :CABI, 2008)
This book (28 chapters), which is the 17th volume in the Crop Production Science in Horticulture Series (18 volumes that focus on scientific principles underlying production practices for economically important horticultural crops from major production systems in temperate, subtropical and tropical climatic areas), summarizes the available information regarding the origin, taxonomy, breeding, physiology, agronomy, pathology (pests and diseases) and processing of cassava, sweet potato, yams and aroids (mainly Alocasia macrorrhiza, Amorphophallus campanulatus, Colocasia esculenta, Cyrtosperma merkusii and Xanthosoma sagittifolium). This book is for researchers, farmers, students and all stakeholders in developing countries, and for those who are working in international institutions.
Keywords: FF003 - Horticultural Crops, (New March 2000); FF005 - Field Crops, (New March 2000); FF020 - Plant Breeding and Genetics; FF060 - Plant Physiology and Biochemistry; FF100 - Plant Production; FF610 - Viral, Bacterial and Fungal Diseases of Plants, (New March 2000); FF620 - Plant Pests, (New March 2000); QQ050 - Crop Produce; QQ100 - Food Processing (General); QQ500 - Food Composition and Quality; ZZ380 - Taxonomy and Evolution